Bioethanol Production from Several Tropical Wood Species using Simultaneous Saccharification and Fermentation Processes - M. Daud; Wasrin Syafii; Khaswar Syamsu (Wood Research Journal, 2012)
The study was conducted to determine the best method of hydrolysis (saccharification) and fermentation for bioethanol production using simultaneous saccharification and fermentation process. Three different tropical wood species namely gmelina wood (Gmelina sp.), pine wood (Pinus merkusii) and oil palm (Elaeis guineensis Jacq.) were pre-treated using kraft process and then converted into bioethanol using simultaneous saccharification and fermentation (SSF) processes. The pulp produced by kraft process was analized to determine their chemical properties before treatments. SSF was performed in 500 ml fermentors with total slurry of 200 ml. The substrate and nutrient media were autoclaved (121ºC and 20 min). The samples diluted to 2.5% (w/v) of total slurry were used as substrate. The enzyme preparation used commercial cellulase enzyme. The amount of cellulase added was 4 and 8% (w/w) of dry mass of samples. All SSF process was conducted by inoculating yeast Saccharomyces cerevisiae into fermentor in the amount of 10% (v/v) 1.5 x 109 CFU/cc. The SSF experiments run for 96 h, and the data were investigated periodically every 24 h. The results showed total sugar and reducing sugar tended to decrease with time of inoculation whereas ethanol concentration increases significantly. The growth of yeast Saccharomyces cerevisiae tended to incease in initial inoculation and decrease by the end of inoculation. The best method of hydrolysis (saccharification) and fermentation using SSF process for all tropical wood species tested were using cellulase 8% of dry mass (DM) and 10% (v/v) of Saccharomyces cerevisiae which produced bioethanol with concentration of 0.98; 0.57 and 0.51% for gmelina, pine and oil palm respectively and produced yields 11.21, 5.85 and 3.20%, in that order.